KESESUAIAN MATERI LAMAN PODCAST AUDIO LINGUA SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA JERMAN KELAS XI - Kusumadewi, Shelvia; Julaikah, Dwi Imroatu (LATERNE, 2022)
Listening skills play an important role not only in daily life but also in learning activities, especially in foreign language learning. Audio Lingua is one of the internet-based pages that contains German-language to support the listening skills. Not only has a variety of themes, this page also provides a feature to select podcasts based on several categories, which are language level, duration, and type of speaker. With all these features, Audio Lingua can be an alternative to support the delivery of learning materials in a practical, effective, and fun way. However, this page cannot be used as a learning medium because the material in the podcast must be adjusted in advance based on the applicable learning curriculum criteria. Therefore, the problem formulation in this article is about the material suitability of the Audio Lingua podcast page as a learning media for listening skills in German learning for the 11th grade in 2 nd semester. According to the problem formulation, this article has a purpose to describe the analysis results of the material suitability of Audio Lingua podcast page as a learning medium for listening skills in German learning for the 11th grade in 2nd semester. The method used by the author is qualitative method and literature study. The literature review in the article includes the theory of experts regarding listening skills, learning media, and the 2013 curriculum. The analysis process uses content analysis techniques by entering data into the table of conformity instruments which is based on the 2013 curriculum. Based on the results of the analysis, it was concluded that out of fifteen podcasts there was one podcast on the Audio Lingua page that met all the criteria for the 2013 curriculum with the theme Tagesablauf, namely a podcast with the title Lena: Mein Alltag.